E-tourism: young consumers’ perceptions on the service quality of tourism related websites / Anderson Ngelambong, Jazira Anuar and Saerah Saien - Ngelambong, Anderson; Anuar, Jazira; Saien, Saerah (2009)
As the internet has become a prominent global phenomenon, many service industries have sought to utilize e-services (electronic service) in order to exploit the internet as a viable alternative marketing channel. Arguably, the group within society today most likely to use the internet as a primary source of information gathering and as a purchasing medium is people from the aged of 18-35 years. Many young people have grown up in the ‘age of technology’, suggesting that they are willing to utilize the internet in their information search and decision making processes. As online suppliers evolve their business operations to incorporate the use of the internet as leverage for competitive advantage, the flow-on effect of such action is to raise the bar for other organizations with increasing customer expectations and perceptions regarding the possibilities and quality of e-service. This, in turn, fuels the need for greater efficiency and effectiveness in customer contact areas and service components within the virtual world. Although the literature on service quality is abundant (Parasuraman, Berry, Zeithmal 1991; Cronin & Taylor 1992; Carman 1990), very little research has, to date, been conducted on the customers’ evaluation of the quality of services delivered over the internet (Cox & Dale 2001), specifically by tourism-related web sites. Organizations that have been experienced and successful in offering e-services are starting to apprehend that besides web site presence and low price, the important success or failure factors also include the quality of services provided online. It is therefore, the aim of this research to provide online tourism suppliers a better understanding of how young consumers perceive and evaluate the quality of electronically offered services. Also, it identifies web site attributes that are valued as important by them when purchasing online. As such, this will lead to the improvement of service as well enhancement as of customer satisfaction and intention to purchase. A quantitative self administered questionnaire was developed and administered to 500 respondents aged 18 to 35 years on location at Universiti Teknologi MARA Shah Alam, Universiti Malaya and Islamic International Universiti. The study data was then analyzed using frequencies, cross-tabulations, chi-squares, one way ANOVA and Kolmogorov-Smirnov Test. The study results showed that a majority of respondents surveyed enjoyed using the internet for information search significantly those in the age group of 24-30, and perceived the internet as a useful information tool. Other than that, those who were in the age range of 30-35 years, and those respondents who have post¬graduate level qualification, were significantly more likely to have longer than five years internet usage experience. In terms of web site service quality, a majority of respondents studied were generally satisfied with the service provided by tourism-related web sites. However, the security and privacy, and personalization dimensions deserve considerable attention from online tourism suppliers for further improvement. Significantly, web site security and privacy, and quality of information were identified as two of the most important determining factors when purchasing online. Based on the results of the analysis of the empirical data, theoretical and practical implications are discussed. The findings of this study support the argument that the internet is indeed a powerful and important tool used by travelers when searching for information and services related to the travel and tourism industries. In addition, the research provides some clear insight as to how online tourism suppliers might better service their e-savvy consumers who seek particular or more personalized travel and tourism related services via the internet.